The Nuss procedure for pectus excavatum during atrial septal defect closure through a minimal right oblique infra-axillary thoracotomy: A case report. Issue 3 (January 2019) - Yang, Guangxian; Deng, Xicheng; Yang, Yifeng; Wang, Jinhua
Abstract: Rationale: Pectus excavatum (PE) is normally an isolated congenital disorder, but it can also occur with congenital heart defect (CHD). The optimal strategy for the management of children with PE and concurrent CHD remains under debate. The surgical strategy has evolved over the last 20 years from staged repair to simultaneous repair of both defects. We present a case of using the Nuss procedure for PE during atrial septal defect (ASD) closure through a minimal right oblique infra-axillary thoracotomy. To our knowledge, this is the first report to describe the correction of PE and CHD by this approach. Patient concerns: A 3.6-year-old patient weighing 13 kg was admitted for elective repair of PE and an ASD. Diagnoses: Clinically, the patient had typical features of PE with chest computed tomography (CT) revealing a Haller index of 4.4 and a grade 2 systolic murmur being heard the loudest at the 2nd−3rd intercostal space, abutting the left sternal border. Echocardiography confirmed a 2-hole secundum ASD with the upper defect being 8 mm, the lower defect 5 mm, and the 2 holes being 5-mm apart, which was deemed unsuitable for interventional closure. Interventions: After discussion with and consent from the family, the child underwent concomitant surgery for both defects. We performed an ASD repair under cardiopulmonary bypass (CPB) on the beating heart through the right oblique infra-axillary thoracotomy, and then, the standard Nuss procedure was performed using a 9-inch bar. Outcomes: Satisfactory ASD closure was confirmed by postoperative echocardiography. Satisfactory PE correction was confirmed by physical examination and postoperative chest radiography. The postoperative recovery process was uneventful, and the patient was discharged 6 days postoperatively. Lessons: This case shows that in carefully selected cases with concomitant PE and ASD, a combination of the Nuss procedure and ASD repair by CPB through infra-axillary thoracotomy can be safely performed, avoiding sternal incision, which leads to bleeding and sternal dehiscence, and results in better aesthetic and surgical outcomes.